Nanometer-size metal complexes : magnetic materials and DNA probes - Di Trapani, Antonella (Trinity College (Dublin, Ireland). School of Chemistry, 2004)
The work described in this thesis was carried out as part of the European TMR Network “Nanometer-size metal complexes” (Contract N ERBMRXCT980226). The synthesis of Cr(III) homoleptic and heteroleptic polypyridyl complexes is presented ([Cr(LL’)2(LL”)]3+ where LL’=LL”= bipy, phen, phendione, dpq, dppz and tpphz or LL≠LL”, LL’= bipy, phen and LL”= phendione, dpq, dppz and tpphz). A study of the absorption properties of these complexes is presented. Crystal structures of [Cr(LL)2X2]+ where LL= bipy or phen and X= Cl' and [Cr(LL)3]3+ where LL= phen and Me2phen are presented and analysed. Fe(II) homoleptic complexes are investigated ([Fe(LL)3]2+ where LL= phen, dpq, dppz and tpphz). [M(phendione)3]n+ (where M= Fe(II), Co(II/III) and Cu(II)) have been synthesized and characterized and their crystal structures are presented. The magnetic moments of these paramagnetic and diamagnetic complexes are studied. DNA binding of some Cr(III) homoleptic complexes ([Cr(LL)3]3+ where LL= bipy, Me2bipy, phen, Me2phen) is investigated by UV/Vis, circular dichroism (CD) spectroscopy, emission spectroscopy and melting studies. The binding constants of these complexes are ~8*10-3 M-1. Temperature dependence induced circular dichroism (ICD) allowed calculation of the thermodynamic parameters of [Cr(phen)3]3+. Preliminary studies were also carried out on two heteroleptic Cr(III) complexes ([Cr(phen)2(LL)]3+ where LL= phendione or dppz). The synthesis of binuclear and tetranuclear complexes made of Cr(III) and Ru(II) metal centres and tpphz bridging ligand is presented. The tetranuclear complexes were also synthesized with Fe(II), Co(II), Cu(II) and Co(III) metal cores and Ru(II) terminal metal centres. The preliminary synthesis of some Cr(III) complexes with a tetrapodal ligand, TPA, is described.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin